Livestreaming from the bedroom: Performing intimacy through domestic space on Twitch. (June 2021) - Ruberg, Bonnie 'Bo'; Lark, Daniel
This article looks at the appearance of domestic spaces on the popular livestreaming platform Twitch.tv, with a focus on livestreams that appear to be shot in streamers' bedrooms. Many Twitch streamers broadcast from their homes, making domestic space central to questions of placemaking for this rapidly growing digital media form. Within the home, bedrooms merit particular attention because they carry particular cultural connotations; they are associated with intimacy, embodiment, and erotics. Drawing from observations of gaming and nongaming streams, we map where bedrooms do and do not appear on Twitch. We locate the majority of bedrooms in categories that foreground connections between streamers and viewers, like Just Chatting, Music & Performing Arts, and autonomous sensory meridian response (ASMR). By contrast, across a wide range of video game genres, bedrooms remain largely absent from gaming streams. The presence of bedrooms on Twitch also breaks down along gender lines, with women streaming being far more likely to broadcast from their bedrooms than men. Here, we build from existing research on both livestreaming and digital placemaking to argue for an understanding of place on Twitch as fundamentally performative. This performance is inherently gendered and bound up with the affective labor of streaming. In addition, we demonstrate how the bedroom, even when it does not appear on screen, can be understood as a 'structuring logic' of placemaking on Twitch. Given the history of livestreaming, which grows out of women's experiments with online 'lifecasting', the bedroom sets expectations for the type of spatial and emotional access a stream is imagined to offer viewers. In this sense, the absence of bedrooms in gaming streams can be understood as a disavowal of intimate domestic space: an attempt by predominantly male streamers to distance themselves from the implicit parallels between livestreaming and practices like webcam modeling.